In vivo evaluation of ocular inflammatory responses in experimental diabetes. Issue 8 (15th July 2005) - Tamura, H; Kiryu, J; Miyamoto, K; Nishijima, K; Katsuta, H; Miyahara, S; Hirose, F; Honda, Y; Yoshimura, N
Abstract : Aims: Diabetic patients may have abnormal inflammatory reactions to foreign or endogenous stimuli. This study was designed to evaluate inflammatory reactions in the diabetic eye through retinal leucocyte dynamics in the inflamed eyes of diabetic rats. Methods: Three weeks after diabetes induction in Long-Evans rats, endotoxin induced uveitis was produced by footpad injection of lipopolysaccharide (LPS). After LPS injection, leucocyte behaviour was evaluated in vivo by acridine orange digital fluorography. Results: The number of rolling leucocytes increased in a biphasic manner at 12 hours and 48 hours. The number of leucocytes accumulating in the retina reached a peak at 72 hours. The maximal numbers of rolling and accumulating leucocytes in the diabetic retina decreased by 56.3% (p<0.01) and 46.7% (p<0.0001), respectively, compared with the non-diabetic retina. The levels of mRNA expression of adhesion molecules in the retina, which were upregulated after LPS injection, were also lower in diabetic rats than in non-diabetic rats. Conclusion: This study is the first to show that endotoxin induced inflammation is disturbed in the diabetic eye, based on evidence that the leucocyte-endothelial cell interactions stimulated by LPS were suppressed in the diabetic retina. These findings support the theory that ocular inflammatory reactions are impaired in diabetic patients.